Spray schedule for the management of Alternaria blight (Alternaria spp.) of linseed - and R.N. SINGH*, R. SINGH, R.B. SINGH (Indian Phytopathology, 2007)
Field experiments were conducted during 2004-05 and 2005-06 to develop an economic spray schedule of mancozeb 75 WP 0.25% aqueous suspension for the management of Alternaria blight, caused by Alternaria lini Dey and Alternaria linicola Groves & Skolko, of linseed (Linum usitatissimum L.) and to identify most spray-responsive crop growth stage. Three sprays of the fungicide, one each, at maximum branching, flowering and capsule formation resulted in least leaf blight of 14.4 and 11.6%,and bud damage of 14.1 and 8.1%, respectively, in the first and second year. It also resulted in highest 1000-seedweight of 7.8 and 8.0g and seed yield of 1500 and 1510 kg/ha. It was followed by the schedule with first spray at flowering and second at capsule formation, which was at par with it in reducing bud damage in the first year and increasing 1000-seedweight and seed yield during both the years. The latter gave a net return of Rs.3620/ha and benefit-cost (B:C) ratio of 3.2 as against a net return of Rs. 3682 and B:C ratio of 2.5 in case of former. A single spray at flowering stage with B:C ratio of 4.3, however, proved most economical. Flower stage, singly or in combination with maximum branching and/or capsule formation, proved most responsive to protection by way of contributing to higher yields.